IMPLEMENTASI PROGRAM GERAKAN LITERASI MASYARAKAT (GLM) DALAM MENUMBUHKAN MINAT MEMBACA WARGA DI KARANG TARUNA KELURAHAN KETAPANG - Bariqulwan, Fauzan; Dayat Hidayat; Tika Santika (UNIB Press, 2023)
This study aims to examine the implementation of the Community Literacy Movement (GLM) program in fostering the reading interest of residents in Karang Taruna, Ketapang Village. This study employs a qualitative research method to gain an in-depth understanding of the program's implementation. The research questions in this study consist of three inquiries. The first question is how the Karang Taruna Program implements the Community Literacy Movement (GLM) in fostering the reading interest of residents. The second question is what factors support the implementation of the program. Meanwhile, the third question is what factors hinder the implementation of the program. The objectives of this research are to describe the implementation of the Community Literacy Movement (GLM) program in fostering residents' reading interest, identify the factors that support the implementation of the program among residents, and identify the factors that hinder the program's implementation among residents. The findings of this study indicate that the implementation of the Karang Taruna Program through the Community Literacy Movement (GLM) has contributed to fostering residents' reading interest in Karang Taruna, Ketapang Village. Some supporting factors found in the program's implementation include community support and active participation, adequate facilities and infrastructure, and collaboration with relevant parties. However, there are also several hindering factors, such as limited human resources, insufficient budget, and challenges in addressing low reading interest among residents. This research contributes to enriching the understanding of the implementation of the Community Literacy Movement (GLM) program in fostering residents' reading interest. The findings of this study can be used as a basis for enhancing the effectiveness of similar programs in other areas. It is recommended to focus on improving human resources, allocating adequate budget, and developing strategies to overcome the hindering factors in program implementation.